2014
DOI: 10.1186/1471-2164-15-350
|View full text |Cite
|
Sign up to set email alerts
|

Toxoplasma gondii merozoite gene expression analysis with comparison to the life cycle discloses a unique expression state during enteric development

Abstract: BackgroundConsiderable work has been carried out to understand the biology of tachyzoites and bradyzoites of Toxoplasma gondii in large part due to in vitro culture methods for these stages. However, culturing methods for stages that normally develop in the gut of the definitive felid host, including the merozoite and sexual stages, have not been developed hindering the ability to study a large portion of the parasite’s life cycle. Here, we begin to unravel the molecular aspects of enteric stages by providing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
90
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(94 citation statements)
references
References 57 publications
(81 reference statements)
4
90
0
Order By: Relevance
“…GO enrichment and KEGG pathway analyses showed that DEGs involved in the metabolic process and catalytic activity were the most enriched at all time points post-infection. A previous study has reported the upregulation of cell growth/maintenance (Translation and Transcription GO categories) and metabolism (Glycolysis and TCA Cycle GO categories)-related genes in the T. gondii merozoite stage during intestinal infection of mice [26]. This intraepithelial intestinal stage of T. gondii proliferates asexually using endopolygeny, whereby multiple daughters are generated from a single parental organism [27].…”
Section: Discussionmentioning
confidence: 97%
“…GO enrichment and KEGG pathway analyses showed that DEGs involved in the metabolic process and catalytic activity were the most enriched at all time points post-infection. A previous study has reported the upregulation of cell growth/maintenance (Translation and Transcription GO categories) and metabolism (Glycolysis and TCA Cycle GO categories)-related genes in the T. gondii merozoite stage during intestinal infection of mice [26]. This intraepithelial intestinal stage of T. gondii proliferates asexually using endopolygeny, whereby multiple daughters are generated from a single parental organism [27].…”
Section: Discussionmentioning
confidence: 97%
“…Unfortunately, the Pru∆ ku80 strain is not capable of completing the entire life cycle (Wang, Harmon, O'Malley, & Sibley, ; Sibley laboratory, unpublished data), despite the ease of generating gene knockouts in this background. This possibility is especially pertinent as most canonical ROP proteins are downregulated during the life stages in, or derived from, the cat (Behnke Zhang, Dubey, & Sibley ; Fritz et al, ; Hehl et al, ). Several studies have detected putative ROPK transcripts that display upregulation in merozoites and oocysts.…”
Section: Discussionmentioning
confidence: 99%
“…The sexual cycle of T. gondii occurs exclusively in the enteroepithelial cells of the intestine of the felid's host (Behnke et al, 2014) and culminates in the production of oocysts, which are adapted to survive under adverse climatic conditions (Dubey, 2010). Toxoplasma gondii oocysts are shed non-sporulated (non-infective) in cat feces, and in a few days they undergo a sporulation process in the environment and with appropriate climatic conditions they mature to sporulated oocysts.…”
Section: Introductionmentioning
confidence: 99%